Design and Analysis of Expert System Based on Information System to Diagnose Computer Failures Using Forward Chaining Method - Rukun, Kasman; Herawan Hayadi, B.; Syarif Hartawan, Muhammad (International Journal of Engineering and Technology, 2018)
Computer damage is the most common case. Correspondingly, computer knowledge is good enough to anticipate the occurrence of computer malfunctions because computer damage problems are quite complex problems. Diagnose damage to the computer. This study aims to design an expert system designed to determine damage to a computer. The method used in designing this expert system is SDLC (System Development Life Cycle) Waterfall. This expert system design uses the UML (Unified Modeling Language) process, system requirements analysis, hardware and software analysis, and system design analysis.Â Â